2016
DOI: 10.3109/21678421.2016.1172818
|View full text |Cite
|
Sign up to set email alerts
|

ALSUntangled No. 35: Hyperbaric Oxygen Therapy*

Abstract: ALSUntangled reviews alternative treatments for patients with ALS (PALS). Here we review hyperbaric oxygen therapy (HBOT) for ALS, a topic for which we have had 90 requests (1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…4 Such rare ALS Reversal cases have been described since the 1960s. [6][7][8][9][10][11][12][13][14][15][16][17][18] To date, we have identified over 50 such cases with a unique ALS Reversal phenotype, and we have found that this phenotype does not have identifiable common environmental factors. 19 The biological basis for an ALS Reversal is unknown, but in the same way that genetic factors contribute to the etiology of ALS, we have speculated that genetic factors might similarly influence the probability of this unusual reversal of disease course.…”
Section: Introductionmentioning
confidence: 99%
“…4 Such rare ALS Reversal cases have been described since the 1960s. [6][7][8][9][10][11][12][13][14][15][16][17][18] To date, we have identified over 50 such cases with a unique ALS Reversal phenotype, and we have found that this phenotype does not have identifiable common environmental factors. 19 The biological basis for an ALS Reversal is unknown, but in the same way that genetic factors contribute to the etiology of ALS, we have speculated that genetic factors might similarly influence the probability of this unusual reversal of disease course.…”
Section: Introductionmentioning
confidence: 99%